DETERMINATION OF RAW AND PROCESSED BLACK OLIVE CHARACTERISTICS OF SIX CULTIVARS - Y. Ozdemir; A. Ozturk; N. A. Tangu; M. E. Akcay; U. Ozyurt; S. Ercisli (Journal of Animal and Plant Sciences, 2020)
Olives can be used both for table consumption or oil production. For table consumption, curing olives is an ancient process that turns the naturally bitter raw fruit into a deliciously salty, tart snack. This study is aimed to investigate table olive characteristics of raw and processed olives from six cultivar candidates. Cultivar candidates were developed by cross breeding between Gemlik and Edinciksu cultivars. Olive from Gemlik cultivar, genitor and widespread produced table olive cultivar in Turkey, was used for comparison. Fruit and seed size with weight, water content, titratable acidity, pH, hardness, color along with oleuropein absorbance (K345) value, salt, total phenolic content, antioxidant activity and sensory analysis were studied on both raw and processed olives. Results showed that the average fruit weight, titratable acidity, oleuropein absorbance value, total phenolic content and antioxidant activity of raw and processed olives of genotypes were found between 4.3-6.5 and 3.9-6.0 g, 0.27-0.38% and 0.33-0.59%, 1.08-2.52 and 0.16-0.26, 175.22-463.15 and 91.00-113.23 mg gallic acid equivalent/100 g, 2618.73-4296.23 and 130.29-147.26 µM trolox/kg, respectively. Statistically significant difference was observed between raw and processed olive for salt, total phenolic content, antioxidant activity, oleuropein absorbance and hardness. It might be caused by genetic factors, which affect skin and tissue permeability of olives during processing. Result of this study showed that there were differences on physical and chemical characteristics og genotypes and GE379 had highest total phenol content, GE397 had highest fruit weight and second highest total sensory scores and GE366 had highest sensory appearance, taste general appreciation and total scores among processed olives. GE366 and GE397 had more remarkable characteristics for production with spontaneous fermentation than other samples.
Keywords: Cross breeding; genotype; oleuropein; total phenol; antioxidant activity; sensory test